Pengaruh Motivasi dan Disiplin Kerja Terhadap Kinerja Pegawai pada UPTD Puskesmas Rawat Inap Rawa Pitu - Habiburrahman; Surya Mulyawan (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2023)
The purpose of this study was to demonstrate empirically the impact of job motivation and discipline on the performance of employees at the UPTD Rawa Pitu Inpatient Medical Center. The study tested her two independent variables: motivation and work discipline. The study population was the 2022 Rawa Pitu Inpatient Medical Center UPTD Office. The method used was a saturated sample or census, a sampling technique that uses all members of the population as samples. The number employed in this study was 58, as this often happens in relatively small populations. The analytical method used was IBM SPSS Statistics 26 (SPSS 26 version). Research results show that work motivation and discipline have a significant positive impact on employee performance.